Assessing climate change adaptation needs in the agricultural sector: Experiences from the CGIAR Research Program on Climate Change, Agriculture and Food Security - Sova, Chase (2017)
 In the agricultural sector there is an especially urgent need to develop and disseminate adaptation prioritization tools given the prominence of the sector in INDCs to the Paris Climate Agreement.  Adaptation practitioners in the sector are increasingly considering a more holistic view of adaptation planning that, from early in the prioritization process, takes in to account food security considerations and mitigation co-benefits.  The CCAFS-CIAT CSA Prioritization Framework (CSA-PF) was designed to help countries prioritize adaptation interventions in the agricultural and water sectors, drawing on known practices to develop adaptation portfolios that can be scaled out.  Cost-benefit analysis (CBA) alone should not serve as a proxy for prioritization. It is critical that CBA analyses are complemented by qualitative assessments of barriers to adoption and an assessment of environmental and social impacts of adaptation strategies.  Prioritization frameworks are only as good as the data entered into them. National research institutions must plan long-term experiments or data collection schemes to measure the impacts of adaptation interventions on farming systems and to provide future inputs into adaptation prioritization.